Continental-wide population genetics and post-Pleistocene range expansion in field maple (Acer campestre L.), a subdominant temperate broadleaved tree species - Eric Wahlsteen; Evangelia V. Avramidou; Gregor Bozic; Rida Mohammed Mediouni; Bernhard Schuldt; Halina Sobolewska (Tree Genetics & Genomes, 2023)
Acer campestre L. is a rarely silviculturally managed and poorly investigated European tree species which forms seminatural populations and can thus be considered as a model tree for studying post glacial colonisation and phylogeography. Herein, we studied the genetic structure of Acer campestre L. in order to investigate population and genetic diversity clines over the distribution range and for synthesizing the results into a post-Pleistocene range expansion hypothesis. We characterised the genetic diversity and population structure of 61 Acer campestre populations using 12 microsatellite markers. The three detected gene pools are structured geographically creating a longitudinal pattern corresponding with their proposed refugial origin. The results indicated a longitudinal population cline with three strong but highly admixed gene pools. Based on the possible signal from the structure results, a number of phylogeographic dispersal hypotheses were tested using approximate Bayesian computation, and this analysis supported the three refugia scenario with a simultaneous divergence prior to the last glacial maximum. Acer campestre shows a typical decrease in population diversity with northern and western distribution and signatures of surfing alleles in the western expansion axis in 2% of the included alleles. Acer campestre exhibits a high degree of admixture among populations and typical signatures of isolation by distance with no naturally delimited subpopulations. The population structure is rather impacted by geographically, than climatologically means with surfing alleles and alleles strongly limited to geographical areas. Our data also suggest that the population structure still today harbours signatures of post glacial migrations from Mediterranean as well as northern glacial refugia.